2023
DOI: 10.3389/fpsyg.2023.1088268
|View full text |Cite
|
Sign up to set email alerts
|

Features of gut microbiota and short-chain fatty acids in patients with first-episode depression and their relationship with the clinical symptoms

Abstract: ObjectiveTo compare the differences in gut microbiota and short-chain fatty acids (SCFAs; metabolites of gut microbiota) in the serum of patients with first-episode depression and the healthy population and to analyze the relationship between gut microbiota and metabolite SCFAs and the clinical symptoms of major depressive disorder (MDD).MethodsA total of 45 patients with first-episode depression and 22 healthy volunteers were chosen to complete relevant scale evaluations, and feces samples and venous blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Such discrepancies can be attributed mainly to regional variations and clustering algorithm methodologies. Nonetheless, these genera are universally acknowledged as SCFA-producing microbes, and their decreased prevalence is observable in disorders like depression and atherosclerosis ( Yoshida et al., 2018 ; Yu et al., 2023 ). Moreover, these genera exhibited negative correlations with thyroid autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Such discrepancies can be attributed mainly to regional variations and clustering algorithm methodologies. Nonetheless, these genera are universally acknowledged as SCFA-producing microbes, and their decreased prevalence is observable in disorders like depression and atherosclerosis ( Yoshida et al., 2018 ; Yu et al., 2023 ). Moreover, these genera exhibited negative correlations with thyroid autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the MDD group had lower levels of certain gut microbiota, including Akkermansia , Megamonas , the Prevotellaceae NK3B31 group, butyrate-producing bacteria like Lachnospira , Subdoligranulum , Blautia , Dialister , and acetate-producing Streptococcus . This suggests that changes in these intestinal bacteria may be involved in the pathogenesis of MDD [ 61 ]. Additionally, SCFAs, particularly butyrate, acetate, and propionate, are known to possess histone deacetylase (HDAC) inhibitory activity, which leads to transcriptional activation by promoting euchromatin configuration, highlighting their role in epigenetic regulation [ 21 ].…”
Section: Brain and Intestinal Microbiotic Interaction: A Molecular Pe...mentioning
confidence: 99%
“…The gut brain, along with the nervous system, HPA axis and immune system, can influence other organs to regulate both the brain and behavior ( 24 ). The proposed mechanism is through production of metabolites, particularly short chain fatty acids (SCFA) which are used to send signals to the brain via the blood stream ( 27 ). Studies of SCFA production in MDD patients reveal a reduction in butyrate and acetate producers ( 25 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed mechanism is through production of metabolites, particularly short chain fatty acids (SCFA) which are used to send signals to the brain via the blood stream ( 27 ). Studies of SCFA production in MDD patients reveal a reduction in butyrate and acetate producers ( 25 , 27 ). Moreover, SCFAs can cross the blood brain barrier (BBB) and have a role in maintaining its integrity ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation